Daniellia oliveri (Rolfe) Hutch and Dalziel: Antimicrobial Activities, Cytotoxicity Evaluation, and Phytochemical Identification by GC-MS - Nassifatou Koko Tittikpina; Gilbert Kirsch; Raphaël Emmanuel Duval; Patrick Chaimbault; Claus Jacob (MDPI AG, 2022)
During a previous study that identified plants used in traditional medicine in Togo to treat infectious diseases, Daniellia oliveri was specifically reported to treat intertrigo and candidiasis. Consequently, to explore the anti-infective potential of this plant, we investigated the antibacterial and the antifungal activity of the plant's parts, as well as the cytotoxic activities of raw extracts and subsequent fractions, and the chemical composition of the most active fractions. In order to evaluate the antimicrobial activity, MICs were determined using the broth dilution method. Then, the most active fractions were evaluated for cytotoxicity by using normal human cells (MRC-5 cells) via the MTT assay. Finally, the most active and not toxic fractions were phytochemically investigated by GC-MS. Interestingly, all the raw extracts and fractions were active against the bacteria tested, with MICs ranging from 16 µg/mL to 256 µg/mL, while no antifungal activity was observed at 256 µg/mL, the highest tested concentration. Moreover, no toxicity was observed with most of the active fractions. The subsequent chemical investigation of the most interesting fractions led to identifying terpenes, phytosterols, phenolic compounds, and fatty acids as the main compounds. In conclusion, this study demonstrated that D. oliveri possesses valuable antibacterial activities in accordance with traditional use.